ملامح الاختلاف بين ترجمات القرآن الكريم والإنجيل والتوراة: دراسة مقارنة = Differences in the concepts of translating the Quran, Bible and Torah: a comparative study = Perbezaan konsep terjemahan Quran, Injil dan Taurat: satu kajian perbandingan - Abd. Rahman, Akmal Khuzairy; Haji Ibrahim, Majdi (IIUM Press, International Islamic University Malaysia, 2017)
This study aims at conducting a methodological comparison among translations of the three scriptures of Semitic religions; Quran, Gospels and the Torah, in order illuminate certain serious issues as regards the originality of texts along with the distinguishing factors of the original language and their impacts on the creed of the three religions. The study further attempts to explore the reasons of emerging different views among the three religions with regard to whether the translated form of a scripture gains possesses the position of its original version or not. In other words, a translated version of the Quran, for example, is never considered a substitute of the original Quran in the real sense of the word. Rather, its authenticity does not go beyond a status of commentary. In contrast, the Gospels are considered a real substitute of its original by the Christians in terms of divine sanctity and authenticity. However, the case of Old Testament is quite different because Jews hold that a translated version of the Old Testament does not supersede its original form whereas the Christians believe that it certainly does. It is because the Christians hold that the Old Testament (especially the Pentateuch) constitutes a considerable part of scriptures that belong to both Christianity and Judaism. The study will reveal a wide spectrum of opinions regarding the acceptability of translated religious scriptures by inducting both Arabic and non-Arabic texts and mainly adopting two methods; qualitative analysis and comparative description. The study has adduced that the dichotomy in views with regard to the translated texts are directly related to the originality of texts and attributing a particular language to the original texts. ***************************************************** تحاول الدراسة عقد مقارنة منهجية بين ملامح ترجمات ثلاثة كتب سماوية مقدسة: القرآن الكريم والإنجيل والتوراة؛ بهدف الوقوف على بعض القضايا المتعلقة بأصالة النص والخصائص التي تميز اللغة المصدر وآثار ذلك على الموقف الديني في عقيدة الأديان الثلاثة، وتهدف الدراسة إلى الكشف عن أسباب ظهور وجهات النظر المختلفة في تناول كيفية ترجمة الكتب المقدسة في الكتب الدينية محل الدراسة، فترجمة القرآن في الإسلام لا تعد بديلاً من الأصل لأنها لا تتجاوز منزلة التفسير، بينما تُعَدُّ ترجمة الإنجيل في المسيحية بديلاً من الأصل؛ إذ تتبوأ مكانة الإنجيل الأصلي في الحجية والقدسية، وأما التوراة، فتتخذ ترجمتها موقفين متضادين لدى كل من اليهودية والمسيحية؛ إذ يرفض اليهود أن تكون ترجمة التوراة بديلاً من الأصل، في حين يقبل النصارى اعتماد التوراة المترجمة وإنزالها منزلة الأصل لأن العهد القديم (التوراة) كتاب مقدس تشترك فيه العقيدتان اليهودية والمسيحية، وتنتهج الدراسة المنهجين المقارن والوصفي التحليلي في تقديم وجهات النظر المختلفة التي تناولت ترجمة النص الديني ومكانة الترجمة الدينية عند أصحابها ومناقشتها من خلال استقراء المصادر العربية والغربية التي تناولت ترجمة الكتب المقدسة، وقد استنتجت الدراسة أن الاختلاف في وجهات النظر في الترجمة الدينية يرتبط مباشرة بطبيعة أصالة النص ووضع اللغة المصدر للنص الأصلي. *********************************************** Kajian ini bertujuan untuk membandingkan konsep-konsep terjemahan Al-Quran، Injil dan Taurat dengan membicarakan isu-isu yang berkenaan dengan sumber asal teks-teks tersebut dan juga bahasa asal yang mempengaruhi pegangan-pegangan keagamaan dan teoretikal yang mendasari Islam, Kristian dan Judaisme. Kajian ini juga cuba untuk memberikan penjelasan tentang sebab-sebab yang membentuk pandangan terhadap terjemahan kitab-kitab suci dalam setiap agama-agama tersebut; Islam tidak mengiktiraf terjemahan Al-Quran sebagai alternatif kepada asal tetapi hanya sebagai tafsiran kepada asal; Kristian pula berpendapat yang terjemahan Injil adalah alternatif kepada yang asal dari segi autoriti dan kesuciannya. Terjemahan Taurat pula berada di antara dua kedudukan tadi kerana Kristian dan Judaisme menganggap Taurat sebagai sebahagian daripada kitab suci mereka. Kajian ini menunjukkan bahawa walaupun terjemahan sebagai satu praktis secara umumnya mempunyai asas-asas yang sama namun pandangan dan pegangan terhadap terjemahan kitab suci dalam agama-agama yang disebutkan tadi adalah berbeza kerana dipengaruhi oleh pendapat-pendapat berkenaan dengan keaslian teks dan bahasa sumber. Kajian ini adalah berdasarkan kepada perbandingan, perincian dan analisa pendapat-pendapat tentang isu keaslian teks dan bahasa sumber daripada sumber-sumber Arab dan Inggeris yang dapat menjelaskan perbezaan-perbezaan konsep terjemahan kitab-kitab suci dalam agama-agama tersebut. Di antara kesimpulan-kesimpulan kajian ialah: isu-isu yang berkaitan tentang keaslian teks dan bahasa sumber telah menyebabkan perbezaan dalam pegangan serta tanggapan terhadap terjemahan kitab suci ketiga-tiga agama yang berkenaan.